Download presentation
Presentation is loading. Please wait.
1
Composition of Functions
Lecture 39 Section 7.4 Mon, Apr 9, 2007
2
Composition of Functions
Given two functions, f : A B and g : B C, where B B, the composition of f and g is the function g f : A C which is defined by (g f)(x) = g(f(x)). Note that the codomain of f must be a subset of the domain of g, or else we cannot form the composition.
3
Examples of Composition
Let f : R R by f(x) = 2x + 3. Let g : R R by g(x) = 4x + 5. Find g f and f g. Are they the same?
4
Composition with the Identity
Let f : A B be any function. Let iA : A A be the identity function on A and let iB : B B be the identity function on B. Then iB f = f and f iA = f.
5
Inverses and the Identity
Let f : A B be a one-to-one correspondence and let f –1 : B A be its inverse. Theorem: f –1 f = iA and f f –1 = iB.
6
Inverses and the Identity
Furthermore, we can prove that if g : B A, then g = f –1 if and only if g f = iA and f g = iB. We can use this as a way to verify that a function g is the inverse of a function f.
7
Inverses and the Identity
Let f : R R by f(x) = 2x + 3. Let g : R R by g(x) = (1/2)x – 3/2. Show that g = f –1.
8
Exponents and Logarithms
The functions f(x) = bx and g(x) = logb x are inverses of each other. (What are their domains and ranges?) It follows that blogb x = x and logb bx = x.
9
Exponents and Logarithms
In the equation blogb x = x, take natural logarithms of both sides: ln(blogb x) = ln x, (logb x)(ln b) = ln x, logb x = (ln x)/(ln b). For example,
10
Composition and One-to-one-ness
Theorem: Let f : A B and g : B C be one-to-one. Then g f : A C is one-to-one. Proof: Assume that f and g are one-to-one. Suppose that (g f )(a1) = (g f )(a2) for some a1, a2 A. Then g(f(a1)) = g(f(a2)).
11
Composition and One-to-one-ness
So f(a1) = f(a2) because g is one-to-one. And then a1 = a2 because f is one-to-one. Therefore, g f is one-to-one.
12
Composition and One-to-one-ness
Theorem: Let f : A B and g : B C. If g f : A C is one-to-one, then f is one-to-one, but g is not necessarily one-to-one. Proof: Assume that g f is one-to-one. Suppose that f(a1) = f(a2) for some a1, a2 A. We must show that a1 = a2. Then g(f(a1)) = g(f(a2)).
13
Composition and One-to-one-ness
That is, (g f )(a1) = (g f )(a2). So a1 = a2 because g f is one-to-one. Therefore, f is one-to-one. Now how do we show that g is not necessarily one-to-one?
14
Composition and One-to-one-ness
In the previous theorem, what if we assume also that f is onto? Does it then follow that g is one-to-one?
15
Composition and Onto-ness.
Theorem: Let f : A B and g : B C be onto. Then g f : A C is onto. Proof: Assume that f and g are onto. Let c C. Then there is b B such that g(b) = c because g is onto.
16
Composition and Onto-ness.
Then there is a A such that f(a) = b because f is onto. So (g f )(a) = g(f(a)) = g(b) = c. Therefore, g f is onto.
17
Composition and Onto-ness.
Theorem: Let f : A B and g : B C. If g f : A C is onto, then g is onto, but f is not necessarily onto. Proof: Assume that g f is onto. Let c C. We must show that there is b B such that g(b) = c.
18
Composition and Onto-ness.
Because g f is onto, we know that there is a A such that (g f )(a) = c. That is, g(f(a)) = c. So let b = f(a). Then b B and g(b) = g(f(a)) = c. Therefore, g is onto. Now how do we show that f is not necessarily onto?
19
Composition and Onto-ness.
In the previous theorem, what if we assume also that g is one-to-one? Does it then follow that f is onto?
20
Composition, One-to-one-ness, and Onto-ness
Let f : R+ R by f(x) = x. Let g : R R+ by g(x) = x2. Then g f = iR+, so f is one-to-one and g is onto. On the other hand, f g = |x|, which is neither one-to-one nor onto.
Similar presentations
© 2025 SlidePlayer.com. Inc.
All rights reserved.